Click estradiol dimers with novel aromatic bridging units: synthesis and anticancer evaluation - Jiří Řehulka; Michal Jurášek; Pavel Dráber; Aleksandra Ivanová; Soňa Gurská; Kateřina Ječmeňová; Olena Mokshyna; Marián Hajdúch; Pavel Polishchuk; Pavel B. Drašar; Petr Džubák (Journal of Enzyme Inhibition and Medicinal Chemistry)
Estradiol dimers (EDs) possess significant anticancer activity by targeting tubulin dynamics. In this study, we synthesised 12 EDs variants via copper-catalysed azide-alkyne cycloaddition (CuAAC) reaction, focusing on structural modifications within the aromatic bridge connecting two estradiol moieties. In vitro testing of these EDs revealed a marked improvement in selectivity towards cancerous cells, particularly for ED1–8. The most active compounds, ED3 (IC50 = 0.38 μM in CCRF-CEM) and ED5 (IC50 = 0.71 μM in CCRF-CEM) demonstrated cytotoxic effects superior to 2-methoxyestradiol (IC50 = 1.61 μM in CCRF-CEM) and exhibited anti-angiogenic properties in an endothelial cell tube-formation model. Cell-based experiments and in vitro assays revealed that EDs interfere with mitotic spindle assembly. Additionally, we proposed an in silico model illustrating the probable binding modes of ED3 and ED5, suggesting that dimers with a simple linker and a single substituent on the aromatic central ring possess enhanced characteristics compared to more complex dimers.